Arc characteristics in short electrical arc high-efficiency milling for GH4169. (October 2020) - Li, Xuezhi; Zhou, Jianping; Wang, Kedian; Wu, Tianbo; Xu, Yan; Hu, Guoyu
To solve core problems of slow arc response and unstable combustion, arc movement characteristics and arc action rules in short electrical arc milling are studied using a high-speed acquisition system and the Phantom high-speed camera in this article. To improve arc reignition, the characteristic parameters of arc discharge are determined as a discharge gap of 0.053 mm and discharge time of 2180 μs. A short electrical arc milling experiment with nickel-based superalloy GH4169 is carried out, confirming that the continuous stable discharge of the arc can easily produce a material removal rate of 40 g/min and a tool wear ratio of 0.8%. An SU8010 scanning electron microscope and energy spectrum analyzer are then used to study the erosion mechanism of GH4169 in short electrical arc milling. This article aims to expand the processing range of short electrical arc machining in the field of special material processing to provide experimental and theoretical bases for the development of short electrical arc milling technology theory and methods.